Trends in international distribution of gross world product (United Nations New YorkUS, 1993)
Analyses the effects of using alternative conversion rates on the changes in the distribution of gross world product between countries and regions over time. Covers the period 1970-1989. Uses four types of conversion rates: market exchange rates as published by the International Monetary Fund; purchasing power parties estimates from Penn World Tables; World Bank Atlas conversion rates used by the World Bank and price adjusted rates of exchange developed by the Statistical Division of the United Nations Secretariat. Presents detailed tables.
DC